Analisis Kinerja Pemodelan Data Star Schema Pada Data Perpustakaan - Dini Nurmalasari; Mutia Sari Zulvi; Puja Hanifah (Jurnal Komputer Terapan, 2019)
Lybrary information system whose data began to be organized from 2013 to the present, has recorded 5,477,618 library collections consisting of books, magazines, journals, CDs and so on. While the number of lending transactions continues to grow each year, although the development is not yet significant, it is recorded at around 3% every day. To help the process of analyzing library data patterns, a web-based system has been created using OLAP (Online Analytical Process) technology, with multidimensional data-based data modeling. To prove the simplicity of multidimensional data-based design, access time and join efficiency, in this study the selected data modeling is a star schema. The test results show that the star schema performance in library data is influenced by the amount of data, the cleaning process and the number of joins.